(untitled) (Al-Academy, 2015)
The industrial development and raise the level of income that has emerged clearly in the middle of the last century in many rich and medium rich countries has great influence on the risen of the health care level. Which led to a significant increase in the reconstruction of people over 65 years and this in turn has produced markets for products and services through modifications to the existing products to meet their physical needs. The importance of research also has the universal design of a comprehensive actually so that it covers as much as possible from human physical & cultural activities. The importance of research locally is to concentrate on this subject who has not been taken into consideration so far to accommodate the elderly and people with special needs. One of the important problems of the universal design concept does not cover through its principles adopted in 1992 to include all design activities. The research aims to identify and study the principles of universal design to propose complementary principles covered the social acceptability of the design. As a result reached by this study and the great importance for social acceptability the researcher suggested some of the complementary principles of universal design by measuring social acceptability, in which the possibility of measuring the social acceptability of the product. The following is summary of those results. The design must have positive interaction with different cultures and it should not offend or underestimate any religious or social culture. It must not promote, directly or indirectly to any particular culture or religion or social or political party